2002
DOI: 10.1063/1.1481774
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and mechanical behavior of dye-doped polymer optical fiber

Abstract: The purpose of this article is to study the materials physics behind dye-doped polymethyl metharcylate (PMMA) that is important for the optical fiber drawing process. We report effects of the fabrication process on the mechanical properties of the final fiber. The qualitative degree of polymer chain alignment is found to increase with the drawing force, which in turn decreases with the drawing temperature and increases with the drawing ratio. The chain alignment relaxes when the fibers are annealed at 95 °C wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 13 publications
2
59
1
Order By: Relevance
“…This is approximately 35% larger than the value reported in the bulk material datasheet [29]. Notice that thermal annealing commonly has the effect of lowering E and increasing ductility [48,51]. The curve shape is also likely to change as a result of the annealing process [48].…”
Section: Mechanical Testing Of the Pc Mpofcontrasting
confidence: 44%
See 3 more Smart Citations
“…This is approximately 35% larger than the value reported in the bulk material datasheet [29]. Notice that thermal annealing commonly has the effect of lowering E and increasing ductility [48,51]. The curve shape is also likely to change as a result of the annealing process [48].…”
Section: Mechanical Testing Of the Pc Mpofcontrasting
confidence: 44%
“…Notice that thermal annealing commonly has the effect of lowering E and increasing ductility [48,51]. The curve shape is also likely to change as a result of the annealing process [48]. Figures 5, 6(a), and 6(b) further include the data from the experiments carried out on unannealed GEHR PMMA [54] and TOPAS 8007S-04 [55] 3-ring mPOFs, which were tested in extension for comparison.…”
Section: Mechanical Testing Of the Pc Mpofmentioning
confidence: 99%
See 2 more Smart Citations
“…The widely accepted point is that the principle mechanism of index change is an increase due to the photo-induced polymerization of the unreacted monomers [5,[18][19][20], while laser-induced heating in the irradiated region during the inscription may also contribute to the index change [5]. Previous reports indicated that annealing of the POF before FBG inscription can relieve the frozen-in stress induced by the fiber drawing process [21] and increase the linear operation temperature range of FBGs [22]. However, the effect of annealing on the strain sensitivity performance was not yet considered.…”
mentioning
confidence: 99%